Early sexual debut among young men in rural South Africa: heightened vulnerability to sexual risk?. Issue 3 (27th May 2005) - Harrison, A; Cleland, J; Gouws, E; Frohlich, J
Abstract : Objective: This report examines early sexual debut (<age 15) among young men in rural South Africa including (1) risk behaviours at first sexual experience, and (2) age at first sex as a predictor of later sexual risk. Methods: Analysis of sexual behaviour data for men 15–24 years (n = 314) from representative cross sectional household survey. Results: 13.1% of 15–24 year old men experienced sexual debut before age 15. Men with sexual debut at less than age 15 were more likely to report risk behaviours at first sexual experience: no condom use (19%), a casual partner (26.8%), and not feeling they had been "ready and wanted to have sex" (19.5%). In multivariate analysis, early sexual debut was strongly associated with ⩾3 partners in the past 3 years (OR = 10.26, p<0.01). Conclusions: Men who initiate sex before age 15 form a distinct risk group in this setting. Specific interventions are needed for young men in the preteen years, before sexual debut.